The Ability of Biology Teacher in Creating HOT (Higher Order Thinking) Question in SMA Negeri 1 Wonosari Klaten - Endah Putri Novi Arti; Hariyatmi Hariyatmi (Universitas Sebelas Maret, 2015)
Indonesian Government Regulation Number 74 Year 2008 Article 3 describes that teachers have one of the four competencies covering pedagogical skills in evaluating student learning outcomes. The aim of research is to determine the ability of Biology teachers in the creating HOT question in SMA Negeri 1 Wonosari Klaten. The type of research is descriptive qualitative and data collection techniques which is collected by documentary studies in daily tests and interviews with Biology teacher in SMA Negeri 1 Wonosari Klaten.The data collected from the ability of Biology teacher's to create HOT questions in odd semester of academic year 2014/2015 SMA Negeri 1 Wonosari Klaten, it is analyzed using descriptive statistics. The result showed that the ability of teachers in creating questions HOT 21.2% is about C4 (15.2%), C5 (3.0%), C6 (3.0%) and about LOT 78.8% namely C1 (31.1%), C2 (29.8%), C3 (17.9%). Keywords: ability of teachers, HOT, taxonomy Bloom